Analytical model for Vuilleumier cycle. (May 2020) - Guo, Tao; Jiang, Tao; Zou, Peng; Luo, Baojun; Hofbauer, Peter; Liu, Jingping; Huang, Yuexin
Abstract: The Coefficient of Performance of Vuilleumier cycle with ideal reversible changes is much higher than those obtained in practical machines. In this paper, an analytical model based on Hofbauer's Vuilleumier cycle (HVC) had been developed. The expansion and compression processes in the model were adiabatic. The expansion volume ratios for HVC were defined and formulas for determination of expansion volume ratios were derived. As the HVC is essentially consisted of hypothetical Stirling engine cycle and Stirling cooler cycle, the respective analytical models for Stirling engine cycle and Stirling cooler cycle were investigated firstly. The effects of regenerator effectiveness and expansion volume ratio were obtained. Then, the expansion volume ratios in the HVC were investigated and obtained at various ratios of dead volumes and temperatures. Then, the performance of HVC at various expansion volume ratios were obtained. Furthermore, the expansion volume ratios in a practical HVC machine was investigated. It was in the range of 1.045–1.068 for Stirling engine cycle and 1.091–1.095 for Stirling cooler cycle. The results showed that the performance could be improved by lifting the expansion volume ratios.